Unspecified falls among youth: predictors of coding specificity in the emergency department. Issue 5 (3rd October 2006) - Kaida, A K; Marko, J; Hagel, B; Lightfoot, P; Sevcik, W; Rowe, B H
Abstract : Background: Deficiencies in emergency department (ED) charting is a common international problem. While unintentional falls account for the largest proportion of injury related ED visits by youth, insufficient charting details result in more than one third of these falls being coded as "unspecified". Non-specific coding compromises the utility of injury surveillance data. Objective: To re-examine the ED charts of unspecified youth falls to determine the possibility of assigning more specific codes. Methods: 400 ED charts for youth (aged 0–19 years) treated at four EDs in an urban Canadian health region between 1997 and 1999 and coded as "Other or unspecified fall" (ICD-9 E888) were randomly selected. A structured chart review was completed and a blinded nosologist recoded the cause of injury using the extracted data. Differences in coding specificity were compared with the original data, and logistic regression was undertaken to examine variables that predicted assignment of a specific E-code. Results: A more specific code was assigned to 46% of cases initially coded as unspecified. Of these, 73% were recoded as "Slips, trips, and stumbles" (E885), which still lacks the specificity required for injury prevention planning; 2% of charts had no fall documented. Multivariate analysis revealed that dichotomized injury severity (adjusted odds ratio (OR) = 1.75 (95% confidence interval, 1.11 to 2.78)), arrival at the ED by ambulance (adjusted OR = 5.41 (1.07 to 27.0)), and the availability of nurse's notes or triage forms, or both, in the chart (adjusted OR = 3.75 (2.17 to 6.45)) were the strongest predictors of a more specific E-code assignment. Conclusions: Deficiencies in both chart documentation and coding specificity contribute to the use of non-specific E-codes. More comprehensive triage coding, improved chart documentation, and alternative methods of data collection in the acute care setting are required to improve ED injury surveillance initiatives.